Konstruksi Pendidikan Karakter Berbasis Islam: Studi Bedhol Bhawikarsu di SMAN 3 Malang - Faridi Faridi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This research focuses on the process of understanding the implementation of character education in SMA Negeri 3 Malang through Bedhol Bhawikarsu activities. This activity is organized by and for students in rural communities under the guidance of educators. On one hand, this activity is designed with the hope of internalizing normative values character ​​in students. Therefore, this research will understand the design and implementation of character education models based on normative values. This research uses a qualitative approach to produce descriptive data in the form of written, oral, and observable behaviors. Data were collected by interview, observation, and documentation methods, and then analyzed by interactive analysis of Miles and Hubermann. This research concludes character education through the direct implementation of Bedhol Bhawikarsu in society can internalize values ​​such as the values ​​of honesty, tolerance, religiosity, patriotism, hard work, and independence. These character values ​​are forms of values ​​that are sourced from Islamic values. Therefore, the construction of the character education organization will be able to be realized through activities that unravel many Islamic values ​​to be internalized in students.